Little Circle Arabic Learning (LCAL) Berbasis Tutor Sebaya untuk Pembelajaran Bahasa Arab di Perguruan Tinggi - Lailatul Mauludiyah (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
Nowadays, there are many problems in using methods found by higher students in the teaching and learning process of the Arabic language, for that it is necessary to have an update in the learning method. The purpose of this study is to develop a peer tutoring based Arabic learning model. From this development, it is expected to be a solution to the survey on the Arabic learning system in the Arabic Language Teaching Program, and the learning system is still classical. The classical learning model is less attractive to students. Because what happens is one-way communication. While the ideal language teaching is to use two-way communication, and students are more active. Also, the problem of class management is a concern. Language learning using large classes is considered less effective. This study uses a qualitative approach to explain the results of validation from media experts and learning methods. The stages of data analysis in this study are data reduction, data presentation, conclusion drawing. This LCAL learning model is developed through constructivism theory and peer tutoring methods. Which lecturer will work with students who have a high ability to manage the class, and the class used is a small class with 10 class members. The output of this study is a recommendation of the Arabic learning model to create a pleasant and not boring foreign language learning atmosphere so that it can achieve the desired Arabic learning target.